2021
DOI: 10.1097/ico.0000000000002880
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Corneal Transplantation in Acanthamoeba Keratitis: Penetrating Versus Lamellar Keratoplasty

Abstract: The purpose of this article was to compare clinical outcomes between therapeutic penetrating keratoplasty (TPK), therapeutic deep anterior lamellar keratoplasty (TDALK), and optical penetrating keratoplasty (OPK) in Acanthamoeba keratitis.Methods: A literature search was conducted in online libraries from 1980 to 2021. The primary end points were best-corrected visual acuity (VA), graft survival, and infection recurrence. In addition, we enrolled 35 consecutive patients with AK from our practice evaluating bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In such cases, prompt surgical intervention is necessary including corneal transplantation with high risk of rejection and recurrence of primary infection. 11 Then, early diagnosis and prompt initiation of treatment are essential for a good and fast visual recovery. Several studies have found that PHMB monotherapy is an effective treatment in AK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, prompt surgical intervention is necessary including corneal transplantation with high risk of rejection and recurrence of primary infection. 11 Then, early diagnosis and prompt initiation of treatment are essential for a good and fast visual recovery. Several studies have found that PHMB monotherapy is an effective treatment in AK.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, prompt surgical intervention is necessary including corneal transplantation with high risk of rejection and recurrence of primary infection. 11…”
Section: Discussionmentioning
confidence: 99%
“… 21–23 In addition, the transplant failure rate in these cases exceeds that in many other indications for keratoplasty, and so those patients undergoing a corneal transplant are often finally left with a poor visual outcome, due to early failure, rejection or disease recurrence. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The latter is of particular concern as it is presumably done in a quiet eye post completion and withdrawal of AAT. [ 120 ]…”
Section: Pack–cxlmentioning
confidence: 99%